1995
DOI: 10.3139/217.950105
|View full text |Cite
|
Sign up to set email alerts
|

Solids Conveying and Melting in a Starve Fed Self-wiping Co-rotating Twin Screw Extruder

Abstract: A flow visualization study of starve fed solids conveying in single screw and a modular self-wiping co-rotating twin screw extruder is observed inflow visualization experiments. Single screw extruders exhibit forward Archimedean transport of material on the undersides of the screw. Self-wiping co-rotating twin screw extruders conveying forward in the intermeshing region and in the region near the apex between the screws. Observations are reported of the melting of solid pellets and possible melting mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 3 publications
3
30
0
Order By: Relevance
“…No differentiated studies were conducted into the influence of the staggering angle, the width of the kneading disc or the process parameters. Intensively investigations have also been carried out by Bawiskar and White [11]. They observed that melting generally is initiated in the screw region prior to the kneading blocks but largely occurs and is completed in the kneading disc blocks.…”
Section: State Of the Artmentioning
confidence: 97%
“…No differentiated studies were conducted into the influence of the staggering angle, the width of the kneading disc or the process parameters. Intensively investigations have also been carried out by Bawiskar and White [11]. They observed that melting generally is initiated in the screw region prior to the kneading blocks but largely occurs and is completed in the kneading disc blocks.…”
Section: State Of the Artmentioning
confidence: 97%
“…4a Besides the work conducted by the Polymer Mixing Study, there are some other experimental and theoretical investigations on the heating/melting mechanisms in Co-TSEs. [11][12][13][14][15][16][17][18] The common methods used to study the melting progression were analyzing the carcass taken from the melting section by either pulling out the [12][13][14] screw or using a split barrel after sudden stop 11,15 -18 and "quenching" of the machine. Real-time melting observations were also carried out through installing glass windows in the melting section.…”
Section: The Importance Of Ped To the Heating And Melting Of Polymer mentioning
confidence: 99%
“…Real-time melting observations were also carried out through installing glass windows in the melting section. For example, Bawiskar and White pro- 12,13 posed a melting model similar to the single-screw Tadmor melting model, based on their experimental observations that two stratified layers were formed: the melt layer at the hot barrel surface and a solid bed in contact with the screw. For example, Bawiskar and White pro- 12,13 posed a melting model similar to the single-screw Tadmor melting model, based on their experimental observations that two stratified layers were formed: the melt layer at the hot barrel surface and a solid bed in contact with the screw.…”
Section: The Importance Of Ped To the Heating And Melting Of Polymer mentioning
confidence: 99%
“…With the static visual technique, it is usually necessary to stop the screw rapidly, to cool the screw and barrel, then to push the screw out of barrel. In terms of twin-screw extruder, there have been many literatures [14][15][16][17][18][19][20][21][22][23] in qualifying the melting mechanism during the extrusion process since 1980s. Subsequently, Tadmor 7,8 proposed a classical melting model for the melting process in single-screw extruder based on Maddock's qualitative description.…”
Section: Introductionmentioning
confidence: 99%